Influential Factors of Taekwondo Achievement in Regional Sport Competition - Dhuha, Ahad Agafian; Yogaswara, Andre; Bin Seh abubakar, Sayid Fariz; Widodo, Agung; Muhibbi, Muhammad (Physical Activity Journal (PAJU), 2024)
Endurance is one of the most influential factors in achieving high-performance athletes. The level of maximum oxygen volume or VO2Max describes endurance. VO2Max is the ability to consume oxygen during physical activity. This research examines the influential factors of Taekwondo achievement in regional sports competitions. The method used in this research is a survey to determine VO2Max levels. The research instrument operated is the Multi Fitness Test (MFT) to measure VO2Max levels. The sample in this study was 20 taekwondo athletes from Semarang City. Data results of the physical condition test are divided into five categories: Poor, Under Average, Average, Above Average, and Excellent. The results confirm that VO2Max level is the main factor in achieving the best athlete performance. Athletes who win gold medals have the VO2Max Above the Average category. The conclusion is that most taekwondo athletes in Semarang City have a VO2Max level in the Average Category. Increasing VO2Max training is required to achieve athletes' high performance.